Pituitary Tuberculoma: An Uncommon Pathology - Praveen Kumar Gupta; Sharad Pandey; Deepa Pandey (Indian Journal of Neurosurgery)
Pituitary tuberculomas are extremely rare with only few cases reported in the literature. Intracranial tuberculoma commonly presents with gradual onset of headache and visual disturbances with or without systemic symptoms. We reported such a case who presented with headache without any visual symptoms, occasional vomiting, and significant weight loss. Contrast magnetic resonance imaging scan was suggestive of pituitary macroadenoma. Transnasal transsphenoidal excision of the lesion (microscopic + endoscopic) was done. Histopathological examination revealed possibility of tuberculosis. Patient was put on standard antituberculosis treatment and discharged in a stable condition.